Pengaruh Inflasi, Suku Bunga Bank Indonesia, dan Nilai Tukar Rupiah (USD/IDR) terhadap Indeks Saham Bisnis-27 di Bursa Efek Indonesia (BEI) - Hamzah Haidar Alwi; Lia Nirawati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This research aims to test the influence of macroeconomic factors namely Inflation level, Suku Bunga Bank Indonesia and rupiah exchange rate (USD / IDR) on the Business Stock Price Index-27 simultaneously and partially. The research method used is quantitative method. Research data collection is done by taking data related to macroeconomics from online data search. This study uses secondary data obtained from the official website online in the form of summaries of reports per month. The population in this study is a time series data for 60 months with a time period of January 2016 - December 2020. In this study used saturated sample techniques. So obtained data that amounted to 60 samples of research data. The data analysis technique in this study uses multiple linear regression analysis. The results of analsis from simultaneous testing, it is known that variable Inflation (X1), Bank Indonesia Interest Rate (X2), and Rupiah Exchange Rate (USD/ IDR) (X3) have a significant effect on the Business Stock Price Index-27. Partially Inflation has a positive and significant effect, Bank Indonesia Interest Rate has a negative and significant effect, the Rupiah Exchange Rate has no effect on the Business Stock Price Index-27. Keywords: Inflation, Bank Indonesia Interest Rate, Rupiah Exchange Rate, Business Index-27